Learning under time pressure: Learners who think positively achieve superior learning outcomes from creative teaching methods using picture books. (March 2018) - Tsai, Chih-Yung; Chang, Ya-Han; Lo, Chia-Lun
Highlights: Positive emotions and time pressure will able to enhance the effectiveness of creative teaching with both ways. The creativity and imagination through the performance after adopting creative thinking teaching materials. For creative teaching curriculum, the conclusion of this study can bring a significant practical application value. Abstract: This study aimed to verify the effectiveness of creative thinking-based teaching using picture books in elementary schools, and investigated the effects of positive emotions and time pressure on learners in a creative thinking-based teaching environment. A quasi pretest–posttest experimental design was employed for this study. The findings indicate that through the educational material set "E.T. Thinker, " an appropriate level of time pressure is exerted on learners, triggering positive emotions and improvements in creativity and imagination on the posttest relative to the pretest. The findings of this study illustrate that the positive effects engendered by positive emotions and time pressure can enhance the effectiveness of creative teaching for both the teacher and learners.